Development Of A Group Guidance Model Based On Traditional Mandar Games To Improve Students' Social Skills - Muhammad Junaedi Mahyuddin; Muharram; Abdul Saman (International Journal of Education Management and Religion, 2026)
This study aimed to develop and evaluate a group guidance model based on traditional Mandar games to improve the social skills of junior high school students. The research was motivated by the observed decline in students’ social competencies, particularly in communication, cooperation, and empathy, as a consequence of increased reliance on digital technology and reduced face-to-face interaction in school settings. Traditional Mandar games were selected as the core medium of guidance because they embody local cultural values such as cooperation, respect, empathy, and sportsmanship, which are essential for social development. The study employed a research and development (R&D) approach adapted from the Borg and Gall model, simplified into five stages: needs analysis, model design, initial product development, limited field trials, and final revision. The participants consisted of 25 eighth-grade students at a public junior high school in Polewali Mandar Regency, West Sulawesi, selected purposively based on identified social skill difficulties. Data were collected using expert validation sheets, model practicality questionnaires, and social skills tests measuring cooperation, empathy, communication, and self-control. Data analysis was conducted using descriptive qualitative and quantitative techniques. The findings revealed that the developed model achieved a validity score of 86.4% (very valid), a practicality score of 89.2% (very practical), and demonstrated high effectiveness, as indicated by a significant increase in students’ social skills from pretest to posttest with a gain score of 0.78. These results indicate that the traditional Mandar game-based group guidance model is conceptually sound, easy to implement, and effective in enhancing students’ social skills. The study concludes that integrating local cultural wisdom into group guidance services provides a contextual, engaging, and sustainable approach to social skills development in schools.